Effect of Livestock Grazing on Growth Characteristics of Atriplex Canescens - A. Mohebby; M. Jafari; A. Tavili; S.A. Javadi; E. Zandi Esfahan; M. Ramezani (Desert, 2012)
It has often been stated or implied that grazing is an important factor in the land degradation process, a suggestion supported by various research projects, and this study investigated the effect of livestock grazing on stem height, crowncover, production, basal diameter, stem biomass, litter, leaf-stem index (leaf to stem weight) , root diameter and weight and seed production per individual of the even-aged Atriplex canescens , by comparing two sites (grazed and non-grazed) across Zarand, Shahreiar rangelands located in the southwestern of Tehran, Iran. For this purpose, by using systematicrandom sampling method, four 300 m long transects were set up in each sampling area and ten quadrats were randomly assigned per transect [8] to measure the stem height as well as the crown cover, production, basal diameter, stem biomass, litter, leaf-stem index , seed production per individual and root biomass and diameter were measured at 3 soil depth (0-30, 30-70, >70 cm) with 4 replications within each of the two studied sites, results indicated that, grazing had no significantinfluence on stem height and leaf-stem index but crown cover, production, basal diameter, stem biomass, litter, seed production per individual, root weight and diameter of the even -aged Atriplex canescens were significantly greater than those of the un-grazed site.